Critical Saving Exposed by Investigating Energy Efficiency Performance and Retrofitting Measures in University Campus Buildings: A Comprehensive Case Study - Oraz, Ece; Sozer, Hatice (ASME International, 2023)
Abstract This article investigates the energy performance pattern of a multifunctional educational building and the possible energy-saving strategies. A comprehensive energy model was developed to evaluate the individual and combined effect of various key active and passive retrofit strategies such as building envelope insulation, glazing properties, lighting equipment, and heating, ventilation, and air conditioning (HVAC) systems. Through a detailed assessment, the research aimed to provide a better understanding of each functional requirement assigned for these patterns and their effect on energy performance. The study not only integrated technological advancements but also incorporated energy management aspects such as temperature set points, occupancy levels, and scheduling. The energy audit through simulation revealed that the annual primary energy consumption of 154.49 kWh/m2 for electricity and 103.48 kWh/m2 for gas. The primary source of energy consumption in the building was identified as the natural gas boiler heating system. The most effective strategy is identified as the energy-efficient update of HVAC systems, 25.05% and 55.11% savings could be achieved in electric and total energy consumption with the best-performing energy retrofit package. The study's distinctive approach involves evaluating interventions' diverse impacts on energy consumption parameters, uncovering both positive and negative effects, thus contributing to a holistic understanding of energy retrofit strategies. It introduces the color grading scala, a decision-support guide visually representing each retrofit measure's multifaceted impacts, facilitating informed choices in energy retrofitting projects.